Leigh syndrome with atypical cerebellar lesions - Veiga, M (2019)
Leigh Syndrome is a neurodegenerative disorder caused by mitochondrial dysfunction, with significant phenotypic and genetic heterogeneity. It usually presents in early life, with a severe prognosis. It can be caused by more than 75 different gene mutations, of nuclear and mitochondrial origin, involving all respiratory chain complexes, with less than 25% of Leigh syndrome having mitochondrial DNA mutations. The typical pathologic hallmarks are focal, bilateral, and symmetric lesions in the basal ganglia, thalamus, cerebellum, cerebral white matter and spinal cord gray matter, usually with T2WI and FLAIR hyperintensity. The basal ganglia and thalami frequently present with a pattern of cytotoxic edema. We present one case with clinical and analytical features consistent with Leigh Syndrome, with peculiar imaging features, showing dominant cerebellar edematous changes with unexpected petechial component suggestive of microangiopathy. To our knowledge, these features are unreported and suggest the existence of microvascular lesions. Based on the reported imaging findings, we propose that Leigh Syndrome should be added to the differential diagnosis of acute cerebellitis.